Case Studies for Management Development in Bangladesh - McLean, Gary N. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
Eight case studies appropriate for use in a course in management development were prepared and are provided in this document. The typical case describes a real business situation in which a real manager had to reach a decision. The case gives quantitative and qualitative information that is, or may be, relevant to that decision. Questions for consideration to help students focus on problems of interest conclude each case study. Each of the case studies deals with a different problem and a different cast of characters. The case studies (and problems) are as follows: Bangladesh Sea Products Ltd.--Parts I and II (decision making, labor relations); Sanitation Products of Bangladesh Ltd. (decision making, new product development); Bangladesh Pharmaceutical Products Ltd. (employee motivation, labor relations); XYZ (Bangladesh) Ltd. (employee motivation, labor relations); H & H (Bangladesh) Ltd. (succession, labor relations); ABC (Bangladesh) Ltd. (labor relations); and Towers (Bangladesh) Ltd. (working with the government). Following the case studies are sections on how to write a case study, how to teach using case studies, and how to solve case studies (student notes). (YLB)
Sponsoring Agency: World Bank, Washington, DC.
ERIC Note: Prepared for the World Bank/Bangladesh Management Education and Training Project. For related documents, see CE 046 184-187.
Educational level discussed: Adult Education.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Education; Adult Education; Case Studies; Decision Making; Developing Nations; Employees; Foreign Countries; Higher Education; Labor Relations; Management Development; Motivation; Professional Continuing Education; Teaching Methods; Bangladesh; Government Business Relationship; Reports, Research